(untitled) (CIPEEX, 2025)
Antimicrobial resistance is currently increasing, and based on this, as well as on the characteristics of Ipê-roxo (Handroanthus impetiginosus), popularly known for its medicinal properties, the present study aimed to evaluate the antibiotic activity of hexane and methanol extracts of the plant against bacteria. In the study, in vitro tests were performed using the microdilution technique to determine the Minimum Inhibitory Concentration (MIC) of the extracts, followed by in vivo analyses in larvae. The results indicated that the methanol and hexane extracts were effective against Gram-positive bacteria such as Streptococcus agalactiae and Staphylococcus aureus, but ineffective against Gram-negative bacteria such as Escherichia coli and Klebsiella pneumoniae. In vivo tests confirmed the in vitro efficacy of the extracts, although without statistical significance. This study suggests that extracts of Ipê-Roxo may be potential candidates for the development of new antibiotics against infections caused by Gram-positive bacteria, highlighting the need for further research to validate these findings.